(untitled) (Bangladesh Journal of Medical Science, 2025)
Onychomycosis is one of the most common nail disorders. Neoscytalidium dimidiatum has been recognized among the common cause of onychomycosis that clinically similar to dermatophyte molds. To our knowledge, there are no reports of onychomycosis due to N. dimidiatum from Indonesia. Here, we describe two cases of onychomycosis, affecting females, 70 and 12 years of age. We discuss macroscopic and microscopic identification as well as the choices of antifungal therapy. The presented cases highlight that N. dimidiatum cannot be underestimated as the cause of onychomycosis in tropical and subtropical countries, especially if there were characteristic clinical conditions of dark-pigmented discolorization of the affected nails. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 309-316